Self-Esteem and Social Comparison: A Study of Body Dysmorphic Symptoms among Private University Students in Nigeria - Aluko, Tolulope Evelyn; Daramola, Olabode Olalekan (NIU Journal of Social Sciences, 2025)
Body Dysmorphic Disorder (BDD) is a growing concern globally, particularly among university students. In Nigeria, there is a need for further investigation into how self-esteem and social comparison specifically contribute to BDD symptoms in private universities that face unique social and cultural pressures. This study adopted a cross-sectional design involving 222 participants selected through convenience sampling. Data collection utilized standardized questionnaires that covered demographic details, the Body Image Survey by Lindgren & Pauly (1975), Rosenberg’s Self-Esteem Scale by Morris Rosenberg (1965), and the Social Comparison Scale by Allen & Gilbert (1995). Descriptive statistics, independent t-tests, and multiple regression analyses were employed to analyze the data, indicating that 47.7% of participants exhibited high tendencies toward body dysmorphia (BD), slightly more prevalent in males than in females. Furthermore, the study identified a positive correlation between self-esteem and tendencies toward body dysmorphia (r = .32, p < .05). The results indicated that self-esteem and social comparison significantly influence tendencies toward body dysmorphia, with self-esteem emerging as a robust predictor (R² = .11, F (1, 219) = 13.47, p < .05, β = 1.58, p < .05). There were no significant differences based on gender in the study (t (219) = -0.43, p > .05). The findings suggest that BD in this group may not be specific to any gender, indicating a potential gender-neutral nature. Additionally, students with higher self-esteem may significantly impact body image concerns through self-perception. Furthermore, the absence of strong social comparison underscores the critical role of factors such as media literacy and resilience. Programs promoting authentic self-worth through mindfulness and self-comparison, as well as teaching media literacy, are recommended. Subsequent studies should investigate the components of self-esteem and how they contribute to addressing body image challenges. Keywords: Self-esteem, social comparison, body dysmorphic disorder, body image, gender, undergraduate.